Methane and hydrogen for energy storage - Carriveau, Rupp; Ting, David S-K (The Institution of Engineering and Technology, 2016)
This book describes technologies for generating methane and hydrogen using electricity (P2G) and storing them in materials, for both stationary and vehicular purposes.
Keywords: Hydrogen -- Storage.; elektronické knihy; electronic books